Bisoprolol‐induced thrombocytopenia: A case report. (3rd September 2017) - Mousinho, F.; Mendes, T.; Sousa e Santos, P.; Azevedo, A. P.; Mousinho, G.; Malcata, C.; Viegas, E.; Madureira, B.; Falcão, F.; Gomes, A. P.; Lima, F.
Summary: What is known and objective: Thrombocytopenia, not associated with bone marrow primary disease, is a common clinical problem. The possibility of drug‐induced thrombocytopenia must be considered, especially in hospitalized patients. Drugs can cause thrombocytopenia by several mechanisms including direct bone marrow or other organ toxicity, and immune reactions. Case description: We describe a patient presenting with thrombocytopenia likely related to bisoprolol. What is new and conclusion: We report a case of bisoprolol‐induced thrombocytopenia which resolved with drug discontinuation and steroid therapy. We review the mechanisms involved in drug‐induced immune thrombocytopenia. Abstract : Case of a 52 years old male patient who developed abrupt immune induced thrombocytopenia, due to bisoprolol intake. Graphic showing platelet count through time, along with the description of therapeutic attitudes.